Is constitutionalized media freedom only window dressing? Evidence from terrorist attacks - Christian Bjørnskov; Stefan Voigt (Public Choice, 2020)
Media freedom is often curtailed in the wake of terrorist attacks. In this contribution, we ask whether constitutional provisions that are intended—directly or indirectly—to protect media freedom affect the degree to which press freedom is curtailed after terrorist incidents. We find that neither provisions explicitly protecting media freedom nor provisions that might protect media freedom indirectly (such as those guaranteeing the independence of the judiciary) mitigate the post-terror curtailment of press freedom.
Keywords: K40; Z13; 330; Press freedom; Media freedom; Terrorism; Freedom of expression; Judicial independence; Constitutional political economy; State of emergency; Emergency provisions